Interstate Lawsuits of Ukraine to the ECTHR: Is it Realistic to Achieve Final Judgments? - Vdovichen, Vitalii; Karvatska, Svitlana; Toronchuk, Ivan (Logos Universality Mentality Education Novelty: Law, 2024)
The article examines the problems and prospects of consideration of interstate applications of Ukraine against the Russian Federation by the ECtHR. The article analyzes that the ECtHR is currently considering five interstate cases initiated by Ukraine against the Russian Federation. However, the Russian Federation does not participate in the proceedings on the claims of Ukraine and does not intend to comply with the ECHR judgments. However, the ECHR will continue to consider the applications submitted to the ECtHR after Russia's withdrawal from the Council of Europe. The article proves that today there is no mechanism for enforcement of the ECtHR judgments on interstate claims of Ukraine by the Russian Federation. Since the Russian Federation does not intend to execute the decisions of the ECtHR voluntarily, there remains the option of either enforcing such judgments by the affected Ukrainians individually on the principle of reciprocity in other countries or creating a supranational mechanism for the execution of such decisions. It is indicated that in the future, the ECtHR will be able to consider and award compensation in all existing cases against the Russian Federation. Affected companies and individuals can file a claim for violation of property rights against the Russian Federation only in respect of actions or omissions before September 16, 2022. Nevertheless, even in light of the Russian Federation's withdrawal from the ECHR, all decisions taken before the exit from the ECHR and the CoE must be implemented. Although after the ECtHR has decided on the merits, it takes a long time to decide on just satisfaction. In conclusion, it is noted that the Russian Federation also does not comply with the interim measures demanded by the ECtHR to cease hostilities in Ukraine immediately. At the same time, this procedural decision is vital for considering the case "Ukraine v. Russia - X" on the merits from a historical perspective.
Keywords: ECtHR; interstate applications of Ukrainе; regional and international judiciary bodies; fundamental human rights; responsibility